Wrist joint proprioceptive acuity assessment using inertial and magnetic measurement systems. (April 2019) - Li, Lin; Li, ShuWang; Li, YanXia
Human wrist proprioception is particularly important due to its role in manual dexterity and associated tasks of daily living. Most studies have focused on testing single degree of freedom joints or were only capable of displacing or moving a joint in a single plane, such as flexion/extension of the wrist. The purpose of this study was to examine the effects of both direction and angular level on the accuracy of human wrist position reproduction error. Sixty subjects (all males) without a history of wrist pathology were recruited from a university campus. Subjects performed a position reproduction task in eight directions at three angular levels. The results showed that wrist position reproduction error depends on direction and angular level. Comparable reliability for the intra-observer measurements for wrist range of motion and joint position sense. The orientation of the joint position sense production ellipse is similar to the orientation of the range of motion ellipse, indicating that subjects generated the most accurate in directions where it is easy to generate more range of motion and the lowest accurate in directions where it is not easy to generate more range of motion. Joint position sense decreased in accuracy as the joint angle increased. The position reproduction error depends on the angular level, and subjects overshoot the target angle for the low angular levels (25% range of motion) and undershoot the target angle for high angular levels (75% range of motion). Mapping the human wrist joint position sense ellipse contributes to our understanding of the comprehensive proprioceptive function of the wrist. This technique offers the opportunity to assess all of the directions of proprioceptive function, which in turn may aid in improving therapeutic approaches.